COMPARATIVE ANALYSIS OF SUPPLY CHAIN RESILIENCE IN THE AIRCRAFT INDUSTRY: A CASE STUDY OF BOEING AND AIRBUS - Yaofei, Li; Saptari, Adi; Hanafiah, Hally; Halim, Isa (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Boeing and Airbus are the leading companies in the aircraft industry and both of these companies compete in dominating the global market for commercial airplanes. Boeing is an American Multinational aircraft manufacturer while Airbus is a European multinational aircraft manufacturer. The objective of this paper is to analyze and compare the supply chain resilience of two major aircraft manufacturers, Boeing and Airbus. This comparison includes comparing their response to global disruption such as covid-19 pandemic, component shortage, trade tensions, and political tensions. To compare the global supply chain of Boeing and Airbus, this paper uses the Supply Chain Resilience Framework as a tool of analysis. Supply Chain Resilience Framework is a model to analyze supply chain resilience including principles of redundancy, flexibility, visibility, and collaboration to evaluate how each company manages disruptions. This paper used the qualitative research method by reviewing previous literature. The data collection will be done through reviewing previous researches, journals, articles, official reports, official website of Boeing and Airbus, and any other related resources. Through this comparison using the Supply Chain Resilience Framework, this research presents the research findings, highlighting identification of Key Resilience Strategies and Comparative Analysis of Resilience Factors between Boeing and Airbus. This comparative analysis on the resilience in the supply chain of Boeing versus Airbus emphasizes different strategies and practices each company has implemented to deal with global disruption.